Supramolecular hydrogels formed from poly(viologen) cross-linked with cyclodextrin dimers and their physical properties - Takashima, Yoshinori; Yuting, Yang; Otsubo, Miyuki; Yamaguchi, Hiroyasu; Harada, Akira (Beilstein Journal of Organic Chemistry, 2012)
Supramolecular materials with noncovalent bonds have attracted much attention due to their exclusive properties differentiating them from materials formed solely by covalent bonds. Especially interesting are rotor molecules of topological complexes that shuttle along a polymer chain. The shuttling of these molecules should greatly improve the tension strength. Our research employs cyclodextrin (CD) as a host molecule, because CD effectively forms polyrotaxanes with polymers. Herein we report the formation of supramolecular hydrogels with an α-CD dimer (α,α-CD dimer) as a topological linker molecule, and a viologen polymer (VP) as the polymer chain. The supramolecular hydrogel of α,α-CD dimer/VP forms a self-standing gel, which does not relax (G' > G'') in the frequency range 0.01–10 rad·s−1. On the other hand, the supramolecular hydrogel decomposes upon addition of bispyridyl decamethylene (PyC10Py) as a competitive guest. Moreover, the β-CD dimer (β,β-CD dimer) with VP does not form a supramolecular hydrogel, indicating that complexation between the C10 unit of VP and the α-CD unit of the α,α-CD dimer plays an important role in the formation of supramolecular hydrogels.
Keywords: cyclodextrins; poly(viologen); supramolecular hydrogel

Smart Materials and Structures - Gandhi, M. V.; Thompson, B. S. (Chapman & Hall, 1992)

Handbook of Stimuli-Responsive Materials - Urban, M. W. (Wiley-VCH Verlag GmbH, 2011)

Responsive Polymer Materials: Design and Applications - Minko, S. (Blackwell Pub., 2006)

(untitled) - Beaty, C. E.; Saltzman, W. M. (J. Controlled Release, 1993)

(untitled) - Kim, S.; Healy, K. E. (Biomacromolecules, 2003)

(untitled) - Mahoney, M. J.; Anseth, K. S. (Biomaterials, 2006)

(untitled) - Petka, W. A.; Harden, J. L.; McGrath, K. P.; Wirtz, D.; Tirrell, D. A. (Science, 1998)

(untitled) - Shen, W.; Lammertink, R. G. H.; Sakata, J. K.; Kornfield, J. A.; Tirrell, D. A. (Macromolecules, 2005)

(untitled) - Hennink, W. E.; van Nostrum, C. F. (Adv. Drug Delivery Rev., 2002)

(untitled) - Okumura, Y.; Ito, K. (Adv. Mater., 2001)

(untitled) - Kretschmann, O.; Choi, S. W.; Miyauchi, M.; Tomatsu, I.; Harada, A.; Ritter, H. (Angew. Chem., Int. Ed., 2006)

(untitled) - Liu, Y.; You, C.-C.; Zhang, H.-Y.; Kang, S.-Z.; Zhu, C.-F.; Wang, C. (Nano Lett., 2001)

(untitled) - Liu, Y.; Li; Fan, Z.; Zhang, H.-Y.; Wu, X.; Guan, X.-D.; Liu, S.-X. (Nano Lett., 2002)

(untitled) - Liu, Y.; Li; Zhang, H.-Y.; Zhao, Y.-L.; Wu, X. (Macromolecules, 2002)

(untitled) - Liu, Y.; Song, Y.; Wang, H.; Zhang, H.-Y.; Li, X.-Q. (Macromolecules, 2004)

(untitled) - Harada, A.; Kamachi, M. (Macromolecules, 1990)

(untitled) - Harada, A.; Kamachi, M. (J. Chem. Soc., Chem. Commun., 1990)

(untitled) - Li, J.; Harada, A.; Kamachi, M. (Polym. J., 1994)

(untitled) - Kawaguchi, Y.; Harada, A. (J. Am. Chem. Soc., 2000)

(untitled) - Harada, A.; Adachi, H.; Kawaguchi, Y.; Okada, M.; Kamachi, M. (Polym. J., 1996)

(untitled) - Meier, L. P.; Heule, M.; Caseri, W. R.; Shelden, R. A.; Suter, U. W.; Wenz, G.; Keller, B. (Macromolecules, 1996)

(untitled) - Wenz, G.; Gruber, C.; Keller, B.; Schilli, C.; Albuzat, T.; Müller, A. (Macromolecules, 2006)

(untitled) - Nelson, A.; Belitsky, J. M.; Vidal, S.; Joiner, C. S.; Baum, L. G.; Stoddart, J. F. (J. Am. Chem. Soc., 2004)

(untitled) - Saito, H.; Yonemura, H.; Nakamura, H.; Matsuo, T. (Chem. Lett., 1990)

(untitled) - Ohga, K.; Takashima, Y.; Takahashi, H.; Kawaguchi, Y.; Yamaguchi, H.; Harada, A. (Macromolecules, 2005)